Mechanisms and product toxicity of activated carbon/peracetic acid for degradation of sulfamethoxazole: implications for groundwater remediation. (1st June 2022) - Dai, Chaomeng; Li, Si; Duan, Yanping; Leong, Kah Hon; Liu, Shuguang; Zhang, Yalei; Zhou, Lang; Tu, Yaojen
Highlights: A low-impact scheme for the remediation of groundwater micro-pollution is proposed. We developed a carbon-based catalyst that effectively activated peracetic acid. Activated degradation mechanism and reactive species are elucidated. The toxicity on aquatic organisms has negligible variation during degradation. Abstract: Carbon-based materials activated peracetic acid (PAA) to repair groundwater is an environmentally friendly and low-cost technology to overcome secondary pollution problems. In this study, thermally modified activated carbon (AC600) was applied to activate PAA to degrade sulfamethoxazole (SMX). And the effect of groundwater pH, chloride ion (Cl − ), bicarbonate (HCO3 − ), sulfate ion (SO4 2− ), and natural organic matter (NOM) on SMX removal by AC600/PAA process was studied in detail. PAA could be effectively activated by AC600. Increasing AC600 dose (10–100mg/L) or PAA dosages (0.065–0.39 mM) generally enhanced the SMX removal, the excellent performance in SMX removal was achieved at 50 mg/L AC600 and 0.26 mM PAA. The removal of SMX was well-described by second-order kinetic, with the rate constant (kobs ) of 10.79 M −1 s −1, both much greater than the removal constants of PAA alone (0.034 M −1 s −1 ) and AC600 alone (1.774 M −1 s −1 ). R-O·(CH3 C(O)OO·, CH3 C(O)O·) and electron-transfer process were proved to be responsible for the removal of SMX while HO· and 1 O2 made little to no contribution to the novel PAA/AC600 system, which differs from typical advanced oxidation processes. The SMX can be removed effectively over a wide pH range (3-9), exhibiting a remarkable pH-tolerant performance. Sulfate ion (SO4 2− ), dissolved oxygen (DO), NOM displayed negligible influence on the SMX removal. Bicarbonate (HCO3 − ) exerted an inhibitory effect on SMX abatement, while chloride ion (Cl − ) promoted the removal of SMX. This showed excellent anti-interference capacity and satisfactory decontamination performance under actual groundwater conditions. Furthermore, the degradation pathways of SMX were proposed, there was no obvious difference in the acute toxicity of the mixed products during the degradation process. It will facilitate further research of metal-free catalyst/PAA system as a new strategy for groundwater in-situ remediation technology. Graphical Abstract: Image, graphical abstract